Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/eci.13845
|View full text |Cite
|
Sign up to set email alerts
|

Risk of reinfection and disease after SARS‐CoV‐2 primary infection: Meta‐analysis

Abstract: Introduction A precise estimate of the frequency and severity of SARS‐CoV‐2 reinfections would be critical to optimize restriction and vaccination policies for the hundreds of millions previously infected subjects. We performed a meta‐analysis to evaluate the risk of reinfection and COVID‐19 following primary infection. Methods We searched MedLine, Scopus and preprint repositories for cohort studies evaluating the onset of new infections among baseline SARS‐CoV‐2‐positive subjects. Random‐effect meta‐analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 126 publications
3
46
2
Order By: Relevance
“…And because after the outbreak the whole county was centralized controlled and all infected patients were isolated, thus we assumed that BA2.2 was the predominant version circulating in this region at this time. The re-positivity rate with Omicron BA.2.2 reached 16.4%, which is higher than that in a previous report ( 25 ). In addition, one study reported that reinfection was found in 26 (0.46%) of 5,554 alpha, 209 (1.16%) of 17,941 delta, and 520 (13.0%) of 3,992 Omicron variants ( 26 ).…”
Section: Discussioncontrasting
confidence: 73%
“…And because after the outbreak the whole county was centralized controlled and all infected patients were isolated, thus we assumed that BA2.2 was the predominant version circulating in this region at this time. The re-positivity rate with Omicron BA.2.2 reached 16.4%, which is higher than that in a previous report ( 25 ). In addition, one study reported that reinfection was found in 26 (0.46%) of 5,554 alpha, 209 (1.16%) of 17,941 delta, and 520 (13.0%) of 3,992 Omicron variants ( 26 ).…”
Section: Discussioncontrasting
confidence: 73%
“…Vaccinated subjects were defined as those receiving ≥ 1 dose of the COVID-19 vaccines currently approved ≥ 14 days before the reinfection. The following search strategy was adopted, without language restrictions: (coronavirus * or coronovirus * or coronavirinae * or Coronavirus * or Coronovirus * or Wuhan * or Hubei * or Huanan or "2019-nCoV" or 2019nCoV or nCoV2019 or "nCoV-2019" or "COVID-19" or COVID19 or "WN-CoV" or WNCoV or "HCoV-19" or HCoV19 or CoV or "2019 novel * " or Ncov or "n-cov" or "SARS-CoV-2" or "SARSCoV-2" or "SARSCoV2" or "SARS-CoV2" or SARSCov19 or "SARS-Cov19" or "SARSCov-19" or "SARS-Cov-19" or Ncovor or Ncorona * or Ncorono * or NcovWuhan * or NcovHubei * or NcovChina * or NcovChinese * ) AND (reinfection * or reinfection * or second episode or recurrence * or recrudescence * or relapse * or RCOVID19) (2). The reference lists of reviews and retrieved articles was also screened, for additional pertinent papers (11).…”
Section: Bibliographic Search Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Clarifying the frequency and predictors of SARS-CoV-2 reinfections is crucial to determine the course of the pandemic, and to optimize restriction and vaccination policies (1)(2)(3). Solid evidence is currently available on the frequency of reinfections after the emergence of the Omicron variant: a recent proportion meta-analysis including 15 million subjects recovered from a first infection estimated an overall reinfection rate of 3.3% in the first 3 months of Omicron predominance, likely increasing (2). However, the potential addictive protection conferred by hybrid immunity, generated by the combination of prior infection and vaccination, as compared to the sole natural immunity, remains to be fully disclosed (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first 3 months of the omicron wave, the reinfection rate was 3.31% [95% confidence interval (CI): 1.15–6.53] compared to 0.57% (95% CI: 0.28–0.94) on the alpha wave and 1.25% (95% CI: 0.97–1.55) on the delta wave. 29 These results showed that the pre-existing immunity from prior infection might have less protective effect on the omicron variant.…”
Section: Pre-existing Immune Response From Prior Infections and Vacci...mentioning
confidence: 89%